Guinea-Bissau : Third Review Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Guinea-Bissau's Third Review Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of Performance Criteria (PCs), and Financing Assurances Review. Program implementation for the third review has been satisfactory. Four of five PCs, three of four indicative targets, and six of eight structural benchmarks were met. Corrective measures have been taken in the remaining areas, with several steps already completed. Economic activity has remained robust and there has been good progress in improving public financial management. Maintaining the positive economic momentum will require further strengthening of public financial management to reduce the fiscal deficit and support macroeconomic stability.